(untitled) (European Journal of Economics, Finance and Business Development, 2025)
This article analyzes the impact of mobile phones on students’ learning and educational processes. Mobile phones provide students with access to internet resources, educational applications, and online courses, expanding their knowledge. However, improper use of mobile phones can lead to distractions, time-wasting, and negative psychological effects. The article discusses the importance of using phones effectively and their role in students’ learning process